Active And Passive Fet Mixer - Mustapa, Muzalifah (Universiti Sains Malaysia, 2005)
To accomplish the project for in designing an active mixer and passive mixer, the main problem is to obtain the conversion gain for the active mixer design compared to passive mixer design. From the linearity issue, active mixer design is nonlinear compared to passive mixer design that is more linear. Besides that, the active mixer has better isolation compared to the passive mixer. This project will be created by applying the circuit design into simulation from HP-ADS (Advanced design system) to the circuit board that is appropriate and and analyzation will be made for both designs. The results at the conversion gain, linearity issue, and port-to-port isolation will be compared for both of the design and will be discussed according to the theory. Additionally, all problem that may occur from the design and analyzation will be considered and the inaccurate result from measurement will be discussed. The mixer will be designed in down conversion system. This circuit is designed by using the hardwares and the surface mount chip elements that are in effective cost and applicable with the practical usage. Therefore, the design of mixer and the analyzation can be make without any intricacy. Hopefully the design of the active mixer and passive mixer using FET transistor can be continued and improved for the usage in variety of application in the future.